2016
DOI: 10.1002/jso.24228
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence in T1‐2N0 gastric cancer in the United States and China

Abstract: Introduction Recurrence patterns after curative intent gastrectomy for T1-2N0 gastric adenocarcinoma are poorly defined. We sought to assess timing, patterns, and risk factors for recurrence in patients treated at two high-volume gastric cancer centers in the United States and China. Methods Between 1995 and 2011, 1,058 patients underwent curative intent gastrectomy. Recurrences were classified as locoregional, distant, or peritoneal. Univariate and multivariate analyses were performed to identify risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…23,24 In a study of 1,058 patients receiving curative intent gastrectomy for T1-2N0 gastric adenocarcinoma in the United States and China, 7% of the patients experienced recurrences during a median follow-up of over 5 years, almost all of which occurred between 6 months and 3 years postoperatively. 25 There is no available evidence supporting routine surveillance for asymptomatic cancer recurrence after curative gastrectomy. Hence, routine intensive radiological evaluation or endoscopy for secondary cancer surveillance is not recommended, especially after 5 recurrence-free years.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In a study of 1,058 patients receiving curative intent gastrectomy for T1-2N0 gastric adenocarcinoma in the United States and China, 7% of the patients experienced recurrences during a median follow-up of over 5 years, almost all of which occurred between 6 months and 3 years postoperatively. 25 There is no available evidence supporting routine surveillance for asymptomatic cancer recurrence after curative gastrectomy. Hence, routine intensive radiological evaluation or endoscopy for secondary cancer surveillance is not recommended, especially after 5 recurrence-free years.…”
Section: Discussionmentioning
confidence: 99%
“…A previously mentioned large retrospective study showed that tumor size ≥ 4.5 cm was significantly associated with worse overall survival in patients who underwent curative gastrectomy [ 8 ]. Tumor size was also one of the independent risk factors for disease recurrence among patients with T1-2 and lymph node-negative stomach cancer in the United States and China [ 23 ]. Additionally, macroscopic tumor size (≥7 cm) was one of the most important risk factors for peritoneal recurrence in patients with advanced stomach cancer who underwent adjuvant chemotherapy after D2 gastrectomy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several large-sample clinical studies across major regions of the world demonstrated that GC PM is a long-standing but ignored clinical problem (Table 1) [7][8][9][10][11]. These studies at different time periods and through different geographic regions have provided convincing evidence that PM is the most frequent and aggressive type of GC metastasis, and it remains the most important challenge in GC treatment.…”
Section: Importance Of Pm In Gc Patientsmentioning
confidence: 99%